Nota NJP 2005 = Report NYP 2005 (Ministry of Education and Community. Department of Youth Affairs ParamariboSR, 2005)
Presents an overview of the history of National Youth Parliament of Suriname and a brief description of its present situation. Records the proposals made by the Board of the National Youth Congress to the government. The proposals cover education, sports and recretion, information, and social welfare and social affairs.
Keywords: EDUCATION